78 Improving psychiatric emergency plans in Scotland. (16th November 2020) - Fletcher, Anna; Connolly, Moira; Morgan, Graham; Manders, Mark; Chopra, Arun
Abstract : Aim: To create a template Psychiatric Emergency Plan (PEP) for use by Scottish Health Boards when reviewing their PEPs. Background: PEPs are reviewed by health boards on a regular basis and at least every five years. PEPs are recommended by the Mental Health (Care and Treatment) (Scotland) Act 2003 Code of Practice as a means to help manage the detention of a patient and aspects of multi-agency working. They are also recommended by the Police Scotland Standard Operating Procedure in dealing with patients who present in mental health crisis. Methods: We incorporated the view of patients and carers, Police Scotland, Scottish Ambulance Service, Emergency Departments, and from our own team with practitioners with a background in General Adult Psychiatry and Social Work in creating the template. We reviewed PEPs from each Scottish Health Board using our template to establish whether the template could be used to help improve quality of PEPs in Scotland. Outcomes: From our consultation process, we found 14 broad themes which we felt were a priority to consider within a PEP: Initial contact; Place of Safety; Alcohol and Substance Misuse; Transport; Resolving Disputes; Assessment; Sharing Information; Missing Patients; Young People; Carers and Patients with Caring Responsibilities; Homelessness; Learning Disability and Autism; Aftercare; Use and Relevance of PEP. In total our template consisted of 63 requirements. We found that there was no heading which had not been addressed by any health board but that many requirements had not been met by all health boards. Conclusions: We have designed a template which addresses broad themes considered in most health boards already. However, not all our requirements were met by every health board. Our template could be used to raised the standard of Psychiatric Emergency Plans and therefore raise the standard of care and patient experience in Scottish Health Boards.